2017
DOI: 10.1136/bmjgh-2016-000260.16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Bacterial Load Assay: A Fast and Accurate Means for Monitoring Tuberculosis Treatment Response

Abstract: BackgroundTuberculosis is a difficult disease to treat. We report a multi-centre performance evaluation of the molecular bacterial load assay (MBLA) that monitors change in patient bacterial load (BL) as they respond to TB therapy.MethodsSmear or Xpert MTB/RIF-positive patients were prospectively monitored for treatment response using MBLA and culture at four sites in Southeast Africa. Treatment response was defined as decline in BL and or rise in time to culture positivity (TTP) or conversion to negative cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…As measures of viability, MGIT TTP and molecular bacterial load are inversely correlated [ 9 , 10 ]. Given the many MGIT negative results, we explored whether this was due to loss of viability by testing the correlation between SDP/OM-S MGIT TTP and bacterial load measured by MBLA among same-day samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As measures of viability, MGIT TTP and molecular bacterial load are inversely correlated [ 9 , 10 ]. Given the many MGIT negative results, we explored whether this was due to loss of viability by testing the correlation between SDP/OM-S MGIT TTP and bacterial load measured by MBLA among same-day samples.…”
Section: Resultsmentioning
confidence: 99%
“…A pre-analytical tool that effectively removes contaminating flora from sputum and preserves viable M. tuberculosis would benefit clinical diagnosis and management of TB disease. Viable M. tuberculosis is required for culture and for molecular assays, such as molecular bacterial load assay (MBLA) which quantifies viable M. tuberculosis in sputum [ 9 11 ], molecular DST [ 12 ] and genomics [ 13 ]. Unlike PrimeStore transport medium, which eliminates viability by killing M. tuberculosis and is only suitable for downstream molecular assays, OM-S maintains viability important for culture and culture-based DST [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This confirms that the test results are reproducible in a high-burden setting. We have shown previously that TB MBLA is species specific confirming the diagnosis 11 14 9 and this provides the healthcare worker with confirmation of the tuberculosis diagnosis.…”
Section: Discussionmentioning
confidence: 59%
“…12 Funded by the EDCTP, the first multi-site evaluation of the test was conducted at the University of Malawi College of Medicine, Instituto Nacional de Saude, Kilimanjaro Clinical Research Institute, and NIMR-Mbeya Medical Research Centre in Malawi, Mozambique, and Tanzania, respectively. 6 The study revealed that MBLA results are reproducible in different laboratory settings and that it is superior to existing tools for the long-term follow-up of TB patients and monitoring treatment response (Figure 2). Unlike culture, wherein reported contamination rates were as high as 30% in some settings, MBLA was found to be unsusceptible to contamination and inhibition.…”
Section: Taking the Mbla Into Policy And Practicementioning
confidence: 86%
“…With funding from the European and Developing Countries Clinical Trials Partnership (EDCTP), partnerships between the UK-based University of St Andrews and research institutions in ES have led to the development of the first ever test -the molecular bacterial load assay (MBLA) -that measures the number of TB bacteria in a patient and reveals if this number is declining as a patient progresses on treatment. 6,7 Assay results are available at the laboratory within 4 hours of sample receipt. Real-time knowl-edge of patient mycobacterial burden and the effectiveness of prescribed medications are crucial for timely clinical decisions on patient management.…”
Section: Introductionmentioning
confidence: 99%